Inositol and human reproduction. From cellular metabolism to clinical use. (1st September 2016) - Milewska, Ewa M.; Czyzyk, Adam; Meczekalski, Blazej; Genazzani, Alessandro D.
Abstract: Inositol is an organic compound of high biological importance that is widely distributed in nature. It belongs to the sugar family and is mainly represented by its two dominant stereoisomers: myo-inositol andD -chiro-inositol that are found in the organism in the physiological serum ratio 40:1. Inositol and its derivatives are important components of the structural phospholipids of the cell membranes and are precursors of the second messengers of many metabolic pathways. A high concentration of myoinositol is found in the follicular fluid and in semen. Inositol deficiency and the impairment of the inositol-dependent pathways may play an important role in the pathogenesis of insulin resistance and hypothyroidism. The results of the research also point out the potential beneficial role of inositol supplementation in polycystic ovarian syndrome and in the context of assisted reproduction technologies and in vitro fertilization. The main aim of the article is to overview the major inositol-dependent metabolic pathways and to discuss its importance for reproduction.